Microparticles Formation of Ganoderma lucidum Extract by Electrospraying Method - Siti Machmudah; Dwi Setyorini; Sugeng Winardi; Wahyudiono Wahyudiono; Hideki Kanda (ASEAN Journal of Chemical Engineering, 2020)
In this work, Ganoderma lucidum (G. lucidum) extract was produced in microparticles form by electrospraying. G. lucidum was extracted hydrothermally at temperature of 160oC and pressure of 7 MPa. The extract solution was subsequently mixed with 6% of Polyvinyl pyrrolidone (PVP) and formed into microparticles by electrospraying process. The electrospraying was carried out at applied voltage of 12, 14, and 16 kV, and the distance between syringe tip and electrospun collector of 8, 10, and 12 cm. The microparticles formed was analyzed using scanning electron microscope (SEM), fourier-transform infrared (FTIR) spectroscopy, and UV-Vis spectrofotometer. The antioxidant efficiency of particles was also analyzed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Based on the SEM analysis, the G. lucidum extract (GLE) – PVP spherical particles were formed by electrospraying. The finer fibres were clearly formed with the increasing applied voltage. The results showed that applied voltage and distance of tip to electrospun collector significantly influence the antioxidant efficiency and the diameter size of particles. The antioxidant efficiency increased with the rising applied voltage and gap of tip to electrospun collector, while the particle diameter decreased with the rising applied voltage and gap of tip to electrospun collector due to fast mass transfer and evaporation. The largest antioxidant efficiency of particles was 0.377/min obtained at 16 kV and 12 cm. It indicated that electrospraying is an effective process to produce pharmaceutical compounds in powder form.